A Study on the Antimicrobial Activity of Algae Extract: The Fucales Order Case - Aurora Silva; Maria Carpena; Stephanie Lopes Morais; Clara Grosso; Lucia Cassani; Frank Chamorro; Maria Fátima Barroso; Jesus Simal-Gandara; Miguel A. Prieto (Biology and Life Sciences Forum)
Over the years, foodborne pathogens have caused countess health problems and massive financial losses. Therefore, an essential goal for the food industry is to prevent food contamination and the related foodborne illnesses as microbial contamination of food items during their acquiring and distribution processes is still a hygienic issue. Moreover, there is an important movement leading to the pursuit of more natural and safe food supplies and ingredients with a special emphasis on the vegan and vegetarian community; as a result, there has been a resurgence in demand for natural and eco-friendly products as a replacement for synthetic ingredients. In this context, and due to their active substances, macroalgae stand out as they are known for possessing antibacterial qualities among other abilities. Because of this, the current study updates our understanding of microbial pollutants in the food industry and compiles the latest updates on the scientific reports on antimicrobial activity of the edible brown algae species with special attention to the algae Bifurcaria bifurcata, Fucus spiralis, and Ascophyllum nodosum. These species which belong to the Phaeophyceae class and order Fucales are reportedly rich in active compounds and are still an undervalued resource. So, the ability of algal extracts to stop the growth of various significant food pathogens is reviewed herein, while considering their advantageous effects on food safety and quality issues.